Vitamin E Improves Neurite Complexity by Enhancing Mitochondrial Function. (7th June 2021) - Park, Han-A; Crowe-White, Kristi; Davis, Abigail; Bannerman, Sydni; Burnett, Garret; Scott, Madison; Broman, Katheryn; Lackey, Kimberly; Licznerski, Pawel; Jonas, Elizabeth
Abstract: Objectives: Neurite outgrowth is a foundational process in brain development and recovery from brain injury. Assembly of the cytoskeleton and formation of new synapses during neurite outgrowth requires an abundance of energy. We have reported that the mitochondrial protein Bcl-xL is necessary for neurite outgrowth and arborization. However, Bcl-xL undergoes post-translational cleavage during oxidative stress resulting in a product that impairs mitochondrial function. Our recent publication demonstrated that treatment with alpha-tocotrienol, an antioxidant member of the vitamin E family, prevents cleavage of Bcl-xL and protects neurons from oxidative stress. In this study, we hypothesize that treatment with alpha-tocotrienol improves mitochondrial function to support the energy demanding processes of growth and development in the neurons. Methods: Primary hippocampal neurons were grown in neurobasal media with or without alpha-tocotrienol for 3 weeks. Then, the number of neurite branches was quantified applying Sholl analysis. We also assayed the ATP/ADP ratio at neurites using the PercevalHR fluorescence biosensor. mRNA and protein levels of total Bcl-xL and cleaved Bcl-xL were measured using real time PCR and immunoblotting. Results: Neurons grown with alpha-tocotrienol achieved more advanced neurite complexity than the control group. Treatment with alpha-tocotrienol enhanced both total ATP and local neurite ATP levels in primary hippocampal neurons. Furthermore, we found that alpha-tocotrienol Increased mRNA and protein levels of Bcl-xL without enhancing post-translational cleavage of Bcl-xL, consistent with our previous study. Conclusions: Our data show that alpha-tocotrienol improves mitochondria-mediated ATP production by enhancing Bcl-xL to support metabolically demanding processes in neurons. We suggest a novel function of alpha-tocotrienol in normal physiological development of the brain. This study also suggests a potential therapeutic role of alpha-tocotrienol in brain diseases associated with neurite injury. Funding Sources: RGC Program (University of Alabama) Crenshaw Research Fund (University of Alabama).